Knowledge Spillover Entrepreneurship and Economic Development - Audretsch, David; Chowdhury, Farzana (Senate Hall, 2011)
This paper seeks to identify whether knowledge spillover entrepreneurship is homogenous across different levels of economic development. Based on a data set measuring entrepreneurial activity at the country level across a broad spectrum of development contexts, the empirical evidence suggests that entrepreneurial activity is related to investments in new knowledge in the context of the most developed countries but not for less developed countries. Keywords: Entrepreneurship, knowledge spillover, growth
Keywords: entrepreneurship|knowledge spillover|growth